(untitled) (Jurnal Bahasa Lingua Scientia, 2014)
This classroom action research was intended to know whether or not KWL (Know, Want, and Learned) technique can improve the ability of the students in comprehending reading in recount text. The researcher was helped by a collaborator and used observation checklist, interview, and questionnaire as the instruments of this research. Besides, she also used reading test to see the improvement of students’ reading comprehension ability in recount text on each cycle. The research started on February 22nd, 2014 and ended on March 8th, 2014. This action research was conducted to the students at SMPN 1 Durenan Trenggalek, class VIIIE. There were 34 students in the classroom. The researcher was conduct the research in two cycles and every cycle had three meeting. The researcher conducted the test three times. They were Pre Test conducted before the strategy was implemented. Post Test conducted at the end of cycle 1 and Post Test conducted at the end of cycle 2. The means score of the students’ reading comprehension test in the pre-test was 60. Then the students‟ mean score of reading comprehension test in cycle 1 improved to 69 and in cycle 2 improved to 80. Based on the result of the study above, it could be inferred that the implementation of KWL (Know, Want, and Learned) was successful in this research, and the KWL (Know, Want, and Learned) technique could be an alternative to improve the students‟ reading comprehension especially recount text.